2018
DOI: 10.1149/2.0741805jes
|View full text |Cite
|
Sign up to set email alerts
|

Odd Random Phase Electrochemical Impedance Spectroscopy to Study the Corrosion Behavior of Hot Dip Zn and Zn-Alloy Coated Steel Wires in Sodium Chloride Solution

Abstract: Electrochemical impedance spectroscopy (EIS) is a very popular technique to investigate the corrosion behavior of metals and alloys in electrolytes. To interpret the EIS data, an equivalent electrical circuit (EEC) is built and the corrosion behavior can be explained on the basis of the values obtained for each element of the EEC after fitting the impedance data. Hence, the reliability of the interpretation greatly depends on the selection of the EEC for the impedance modeling. In this work, odd random phase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The fitting of the Nyquist curves is also shown in Figure S3. Based on the above disclosed facts, the fitting could be considered valid for the interpretation of corrosion occurring at surfaces and interfaces of pristine and LLCE-coated Cu. , The terms in EECs are as follows: R s , NaCl resistance; R ct , charge transfer resistance; W , Warburg impedance; CPE ct , constant-phase element associated with R ct ; CPE f , constant-phase element for LLCE layers; R f , associated LLCE resistance; Ceff ct , effective capacitance derived from CPE ct values; Ceff f , effective capacitance derived from CPE f values; n f and n ct , surface parameters for CPE f and CPE ct . The Ceff for the LLCE coating and pristine Cu were calculated by the formula Ceff = false( Y × R ct 1 n false) 1 / n where Y is the magnitude of CPEs.…”
Section: Resultsmentioning
confidence: 99%
“…The fitting of the Nyquist curves is also shown in Figure S3. Based on the above disclosed facts, the fitting could be considered valid for the interpretation of corrosion occurring at surfaces and interfaces of pristine and LLCE-coated Cu. , The terms in EECs are as follows: R s , NaCl resistance; R ct , charge transfer resistance; W , Warburg impedance; CPE ct , constant-phase element associated with R ct ; CPE f , constant-phase element for LLCE layers; R f , associated LLCE resistance; Ceff ct , effective capacitance derived from CPE ct values; Ceff f , effective capacitance derived from CPE f values; n f and n ct , surface parameters for CPE f and CPE ct . The Ceff for the LLCE coating and pristine Cu were calculated by the formula Ceff = false( Y × R ct 1 n false) 1 / n where Y is the magnitude of CPEs.…”
Section: Resultsmentioning
confidence: 99%
“…Bode phase plots showed that phase angle difference between applied voltage and current response was enhanced with the number of layers, which suggested that charge distribution on the surface was becoming more uniform. Both these observations advocated that corrosion of Cu was effectively prevented 38,39 . Furthermore, Nyquist plots of pristine Cu and SQR coated Cu could be divided in two segments: first, big semi-circular loop; and second, line/incomplete loop in low frequency zone.…”
Section: Discussionmentioning
confidence: 98%
“…Different techniques have been developed to perform impedance measurements with respect to instrumentation, where the most common one is the FRA 4 . However, other approaches such as the use of multisine, 69,147,148 white noise 149,150 or wavelet 151,152 are also used, but their description is outside the scope of this Primer. These techniques have also been used to evaluate other transfer functions involving electrochemical systems such as thermal impedance spectroscopy, 153 electrohydrodynamic impedance [154][155][156] , modulation of the interfacial capacitance 157-160 and local electrochemical impedance spectroscopy.…”
Section: [H1] Limitations and Optimizationsmentioning
confidence: 99%